Stomach Content Analysis of Gariang Fish (Tor sp) At Anai River Padang Pariaman Regency - Karina, Indira (Saintek Perikanan : Indonesian Journal of Fisheries Science and Technology, 2023)
Analysis of fish stomach contents can provide an overview of the composition of natural feed in the stomach with its habitat.The research about stomach content analysis of gariang fish (Tor sp) at Anai River aimed to know the kind of gariang fish’s food include main food, supplement food, and additional food. This is because the economis value of gariang fish is very high but the distribution is still limited and the management has not been carried out optimally. The potensial of gariang fish resources also be threatened due to environmental pollution caused by household and industrial waste. Therefore, it is necessary to have good management to maintained the environmental conditions and the availability of gariang fish food